Infliximab trough levels: A comparison between the Quantum Blue Infliximab assay and the established ELISA. Issue 8 (16th January 2020) - Lim, Ming Han; Aluzaite, Kristina; Schultz, Michael; Casey, Paul
Abstract: Background and Aim: Therapeutic drug monitoring of infliximab (IFX) using the established laboratory‐based enzyme‐linked immunosorbent assay (ELISA) cannot produce results fast enough to allow IFX dose adjustments prior to each IFX infusion. We investigate the validity of IFX trough levels obtained through the Quantum Blue IFX (QB‐IFX) rapid assay compared with the established ELISA. Methods: Adult inflammatory bowel disease patients receiving maintenance IFX infusions at Middlemore Hospital and Dunedin Public Hospital were prospectively recruited from July to October 2016. Serum samples were stored at −40 °C until processed using QB‐IFX by a clinician at Middlemore Hospital and a research staff at Dunedin Public Hospital strictly following the manufacturers' instructions in an open label fashion. Results: Forty four inflammatory bowel disease patients were recruited. Median duration of IFX therapy was 21 months (interquartile range: 12–44). Overall, the correlation between ELISA and QB‐IFX trough levels was 0.73 (95% confidence interval [CI]: 0.53–0.85). The sensitivity and specificity of a QB‐IFX level < 7 in detecting an ELISA level < 7 were 0.79 (95% CI: 0.59–0.92) and 0.75 (95% CI: 0.48–0.93), respectively. Conversely, the sensitivity and specificity of a QB‐IFX level < 2 detecting an ELISA level < 2 were 1.00 (95% CI: 0.52, 1.00) and 0.97 (95% CI: 0.85, 1.00), respectively. Conclusion: The QB‐IFX had excellent sensitivity and specificity for IFX levels < 2 obtained with the established ELISA. Therefore, QB‐IFX could be used for real time dosing decisions when the IFX level is low and dose escalation is required.